A case history:: Dredging and disposal of golden horn sediments - Berilgen, MM; Özaydin, IK; Edil, TB (AMERICAN SOCIETY TESTING AND MATERIALS, 2000)
Rehabilitation of the historic Golden Horn river outlet has been a major concern to people of Istanbul in the past two decades. Currently a major rehabilitation project is being implemented which involves the dredging of bottom sediments in the upstream one third of this waterway to provide for sufficient water depth needed for a clear marine environment and to make navigation possible for small vessels. The stability analyses have shown that the 6 (horizontal): I(vertical) underwater slopes formed by dredging can be sustained. Among the several possible alternatives considered for the disposal of dredged bottom sediments, the most economical and environmentally safe alternative was storage of the sediments at an abandoned rock quarry pit at a distance of about 5 km. A 40-m- high, zoned earth dam constructed at the rock pit site enabled the storage of about 4 million cubic meters of dredged material, which is pumped via a pipeline. The pumped dredgings are undergoing large-strain self-weight consolidation. The paper presents this case history and the associated technical challenges. The geotechnical issues relating to the stability of the dredged channel as well as the result of the laboratory investigations on sedimentation and self-weight consolidation behavior of the dredged materials are presented together with the numerical prediction of field behavior at the disposal site.
Keywords: disposal of dredged material; self-weight consolidation; consolidation; settlement; large strain; numerical modeling; STRAIN CONSOLIDATION; Engineering; Materials Science